Penerapan Metode Multisensori Dalam Mengembangkan Kemampuan Membaca Permulaan Anak Pada Paud Plamboyan 3 Kabupaten Karawang - Samsir Nur Alam; Sutarjo, Sutarjo; Suminar, Uum (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the implementation of the multisensory method in developing early reading skills among children at PAUD Plamboyan 3, Karawang Regency, and to determine the results of this implementation. The study is motivated by the low level of early reading ability in children, indicated by difficulties in pronouncing letters, combining syllables, and understanding words in context. This research uses a qualitative approach with a case study method. Data collection techniques include observation, interviews, and documentation. The findings reveal that the multisensory method incorporating visual (using flashcards with letters and images), auditory (listening to letter sounds via Wordwall media), kinesthetic (writing names with crayons), and tactile activities (pasting letters with origami) significantly improves children’s early reading abilities. Children showed progress in letter pronunciation, syllable and word formation, and reading simple sentences. Moreover, their interest and motivation in reading increased. The conclusion indicates that the multisensory method is effective in holistically and enjoyably developing early reading skills in young children. Keywords: Multisensory Method, Early Reading, Young Children, PAUD